Implementation of Fault-Tolerant Control for a Robot Manipulator Based on Synchronous Sliding Mode Control: An Advanced Study - Le, Quang Dan; Kang, Hee-Jun (New Approaches in Engineering Research Vol. 13, 2021)
In this paper, an active fault-tolerant control for a robot manipulator based on synchronous sliding mode is proposed. As the synchronization errors approach zero, the joint errors tend to become equal and also approach zero. Therefore, the synchronization technique is inherently effective for a fault-tolerant controller. To demonstrate such a system, the following implementation is presented. First, an estimator was designed with an extended state observer to estimate uncertainties/disturbances along with faults/failures. The estimator signal was used for an online compensator in the controller. A fault-tolerant controller with a combination of synchronous sliding mode technique and estimator was proposed. The stability of the system was established using Lyapunov theory. Finally, fault tolerant control was implemented in a three degree-of-freedom robot manipulator and compared to the conventional sliding mode control. This comparison shows the effectiveness of the proposed active fault-tolerant control with synchronous sliding model technique.